Mental health and stressful life events among post graduate Cypriot University Students: A cross-sectional descriptive correlational study - Sokratous, Sokratis; Alexandrou, Giorgos; Kaikoushi, Katerina; Karanikola, Maria (My University, 2022)
Background: Previous findings suggest that stressful life events are linked with mental health status of university students. The aim of this study was to investigate the mental health status and its association with the number and the severity of self-reported stressful life events among post graduate university students in Cyprus. Methods: A descriptive correlational design with cross sectional comparison was used. The General Health Questionnaire-28 (GHQ-28) for the assessment of mental health status and the Life Events scale for Students (LESS) for stressful life events were applied. Both scales were completed anonymously and voluntarily by 90 post graduate students. Results: The mean(± SD) age of participants was 25.03(±2.64) years. The frequency of clinical symptoms of mental distress (GHQ total score≥24) was 36.7% of participants. Statistically significant associations were noted between GHQ-28 subscales and gender. Specifically, males reported higher scores in depressive symptoms subscale (p<0.05). Furthermore, higher scores on both the intensity and number of stressful events were associated with clinical symptoms of mental distress (GHQ total score≥24) (p=0.01; p=0.001, respectively). Conclusions: The high frequency of clinical symptoms of mental distress among post graduate university students, as well as the association with stressful life events, highlights the need for psychological empowerment strategies towards students by institutional counselling services.
Keywords: Life events scale for students; Stressful life events; Cypriot university students; General health Questionary